Factfulness : ten reasons we're wrong about the world - and why things are better than you think - Rosling, Hans, 1948-2017 1948-2017 (Flatiron Books, 2018)
When asked simple questions about global trends--what percentage of the world's population live in poverty; why the world's population is increasing; how many girls finish school--we systematically get the answers wrong. So wrong that a chimpanzee choosing answers at random will consistently outguess teachers, journalists, Nobel laureates, and investment bankers. In Factfulness, Professor of International Health and global TED phenomenon Hans Rosling, together with his two long-time collaborators, Anna and Ola, offers a radical new explanation of why this happens. They reveal the ten instincts that distort our perspective--from our tendency to divide the world into two camps (usually some version of us and them) to the way we consume media (where fear rules) to how we perceive progress (believing that most things are getting worse)